Plant diversity of Petungkriyono Forest of Dieng Plateau, Central Java, Indonesia - Irma Damayanti; Azis N. Bambang; Tri R. Soeprobowati (Society for Indonesian Biodiversity, 2021)
Abstract. Damayanti I, Nurbambang A, Soeprobowati TR. 2021. Plant diversity of Petungkriyono Forest of Dieng Plateau, Central Java, Indonesia. Biodiversitas 22: 3497-3507. Petungkriyono is one of the remaining forests considered as the key biodiversity site in Central Java, Indonesia. The study aimed to analyze the composition, structure, and diversity of flora. The research used 60 circular plots with 0.04 hectares on five sites: Tlogopakis, Kasimpar, Yosorejo, Kayupuring, and Tlogohendro. The result indicated that the forest was dominated by 54.6% mixed forests, 29.1% pine forests, 10.7% puspa forests, and 5.6% unproductive areas. A total of 979 individuals belong to 108 species, among 88 genera and 43 families. The dominant family was Moraceae (32.6%) and has 10 species of Ficus spp as a key pioneer in a dry habitat. According to the Red List, the International Union for Conservation of Nature (IUCN), there were 4 species categories of endangered species (EN), 11 species as vulnerable category (VU), 46 species as least concern (LC), and 45 species not evaluated (NE). The horizontal and vertical structure of trees was dominated by 10-20 cm diameter classes and 82% at a medium level of the Shannon-Weiner index (H’). The conclusion is that plant diversity plays a significant role to maintain ecosystem stability, therefore conservation activities have to be developed properly. Ecosystem services are produced in the social-ecological system to increase human well-being and resilience.